Review Analisis Produk Marketplace Online pada Algoritma Support Vector Machine - Rizqi Agung Permana; Sucitra Sahara (Department of Science and Technology Ibrahimy University, 2021)
With the presence of a marketplace, internet users are able to shop by cellphones or laptops which ease them to process the transactions. This advantage is the key to the popularity of e-commerce and marketplaces in the 21st century. Considering that users prefer having e-commerce to going out and looking for products. Internet users are still hesitant in choosing a good and bad marketplace since there is a disappointing marketplace system and a deficient service. The Researcher will make a selection of the product marketplace based on opinions or review comments. The stage of selecting marketplace products is based on an opinion or public opinion who buys goods on the selected marketplace, the opinion is given into online opinions such as comments on the marketplace. The comments that are used as samples will be processed and grouped into data sets. In this case, the researcher processes the classification or grouping of data by applying the Support Vector Machine (SVM) method in accordance with the classification of processing data sets in the form of text. After being applied to the SVM method, the accuracy value is 75.92%, the SVM method produces a fairly good accuracy value on the dataset in the form of text classification in the marketplace review. From the results of testing the data, it can help readers in determining a good marketplace.